396 IMMUNOMODULATION IN MELANOMA THERAPY. Issue 1 (1st January 2007) - Nguyen, H.; Haskell, J.; Chang, P. L.; Narayan, R.; Tran, T.; Moy, L.; Bruhn, K.; Craft, N.
Abstract : Purpose: Prophylactic administration of a recombinant Listeria monocytogenes (rLM) vaccine expressing the murine tyrosinase-related protein-2 (TRP-2), a melanocyte-derived antigen highly expressed in melanoma, has been shown to induce a functional CD8 + cytotoxic T-lymphocyte (CTL) response that is partially protective against subsequent melanoma challenge. The use of imiquimod, a synthetic Toll-like receptor 7 agonist, in addition to the rLM vaccine, significantly enhanced the antimelanoma response. In this study, we used a mouse model of metastatic melanoma to evaluate the therapeutic potential of the Listeria -based vaccine alone and in combination with imiquimod. Methods: C57BL/6 mice were injected with 5 × 10 3 B16 melanoma cells intravenously and assigned to the following treatment groups: placebo, CRS100 (control LM strain without TRP-2), rLM/TRP2 (LM strain expressing TRP-2), and rLM/TRP2-imiquimod ( n = 8/group). Survival status was monitored for 46 days. To evaluate T-cell responses to the vaccine, additional mice were assigned to the following groups: no tumor-CRS100, no tumor-rLM/TRP2, tumor-CRS100, and tumor-rLM/TRP2 ( n = 4/group). Mice were challenged with tumor and subsequently received vaccine as indicated. Splenocytes were harvested 7 days later. Cells were stimulated with LLO (an endogenous listerial CD8 + T-cell epitope present in both LM strains), NP (a "non-self" epitope present in rLM/TRP2), or TRP2 and then stained for intracellular IFN-γ expression. Splenocytes were analyzed by flow cytomentry and gated for CD8 expression. Results: At 46 days after tumor implantation, the survival rates for the placebo, CRS100, rLM/TRP2, and rLM/TRP2-imiquimod groups were 25%, 25%, 25%, and 50%, respectively. Immunization with the rLM/TRP2 strain also induced CD8 + T cells specific for LLO, NP, and TRP-2 in the presence or absence of tumor. As expected, CRS100 vaccination only generated CD8 + T cells specific for the "self" epitope LLO. Conclusion: Survival was prolonged with the rLM/TRP2 therapy and the antitumor effect was enhanced with adjuvant imiquimod treatment. The rLM/TRP2 vaccine activated CD8 + T cells specific for the "non-self" epitope NP and the "self antigen" TRP-2 regardless of tumor status. These findings indicate that rLM/TRP2 and imiquimod can induce a functional CD8 + CTL response in the presence of tumor, as well as prolong survival. Our results provide further evidence that Listeria -based vaccines against melanoma may represent a practical clinical therapeutic modality.